2021
DOI: 10.1002/jsfa.11157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary ferulic acid supplementation on growth performance and skeletal muscle fiber type conversion in weaned piglets

Abstract: BACKGROUND Ferulic acid (FA) is a common polyphenolic compound. The purpose of this study was to explore the effect of dietary FA supplementation on growth performance and muscle fiber type conversion in weaned piglets. In this study, eighteen 21‐day‐old DLY (Duroc × Landrace × Yorkshire) weaned piglets were randomly divided into control, 0.05% FA, and 0.45% FA groups. RESULTS Our study showed that dietary FA supplementation had no effect on growth performance, but it could upregulate the expression of slow my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…An important clue to the basis of ferulic acid’s versatile protective effects may have been provided by recent studies reporting that, in low micromolar concentrations that are readily achievable with oral supplementation and likely by ingestion of anthocyanin-rich diets, ferulic acid upregulates expression of Sirt1 at both the mRNA and protein level. This effect has been demonstrated in chondrocytes, skeletal muscle fibres, testes, neural stem cells and hepatocytes, and hence may be broad in scope 6–11. Presumably, ferulic acid either upregulates transcription of the Sirt1 gene or prolongs the half-life of Sirt1 mRNA.…”
Section: Upregulation Of Sirt1 By Ferulic Acidmentioning
confidence: 95%
“…An important clue to the basis of ferulic acid’s versatile protective effects may have been provided by recent studies reporting that, in low micromolar concentrations that are readily achievable with oral supplementation and likely by ingestion of anthocyanin-rich diets, ferulic acid upregulates expression of Sirt1 at both the mRNA and protein level. This effect has been demonstrated in chondrocytes, skeletal muscle fibres, testes, neural stem cells and hepatocytes, and hence may be broad in scope 6–11. Presumably, ferulic acid either upregulates transcription of the Sirt1 gene or prolongs the half-life of Sirt1 mRNA.…”
Section: Upregulation Of Sirt1 By Ferulic Acidmentioning
confidence: 95%
“…A recent study in 21-day-old piglets demonstrated that FA could promote muscle fiber type conversion from fast-twitch to slow-twitch via the Sirt1/AMPK/PGC-1α signaling pathway, moreover a decrease of lactate dehydrogenase (LDH) activity, that is positively associated with glycolytic fibers confirming that FA could promote the transformation of muscle fiber type from fast-twitch to slow-twitch. [39].…”
Section: Morphometry Of Muscle Fibersmentioning
confidence: 99%
“…These differences in our study might be because FA does not bind to β 2 -AR and there might be other receptors or other mechanisms that recognize FA and promote muscle deposition. A recent study indicates that FA has mitochondrial and enzymatic pathways that promote fiber type conversion from fast-twitch to slow-twitch and myogenic regulators targeting hypertrophy in oxidative fibers [39]. Therefore, further research is required to confirm the initial action mechanism of FA to promote growth in lambs.…”
Section: Gene Expression In Longissimus Thoracis Musclementioning
confidence: 99%
“…Ferulic acid has shown remarkable anti-inflammatory and antioxidant activity in pre-clinical studies and, as sodium ferulate, is widely used in cardiovascular medicine in China [90,91]. Recent studies have found that this may reflect, in large part, the ability of ferulic acid to up-regulate SIRT1 expression at the mRNA and protein level [92][93][94][95][96][97]. This effect has been demonstrated in a number of cell types, and hence appears to be a general effect; its mechanistic basis remains unclear.…”
Section: Manifold Nutraceutical and Dietary Options For Activation Of...mentioning
confidence: 99%